Developing an instrument for measuring views on Muhammadiyah ideology - Subando, Joko; Samsuri, Muh; Muslimin, Edy (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2023)
This research aims at developing an instrument for measuring views on Muhammadiyah ideology that is valid and reliable. This study adapted Borg and Gall's development model through initial research, planning, initial product development, limited testing, product revision, expanded testing, and product revision. The steps started with initial research to obtain the ideology construct of books related to Muhammadiyah. The ideology construct obtained was used as the basis to arrange instrument items which were then validated by five experts in the fields of measurement, Muhammadiyah ideology, practitioners, and Muhammadiyah cadres by filling the sheet of variable appropriateness with indicators and indicators appropriateness with the statements. The results of the experts' validation were analyzed with the Aiken formula. The validated instrument was then tested limitedly in the Muhammadiyah regional leadership in Karanganyar, Sragen, and Boyolali, by involving 253 respondents. The result of the test was analyzed using factor analysis and SEM using the Lisrel program. The result of the research shows that the instrument for measuring the views on Muhammadiyah ideology consists of 26 items comprised of seven aspects of Muhammadiyah ideology measurement, including tauhid (two items), living in a social group (three items), Allah's law (three items), Islamic doctrine (five items), the prophet's ittiba' (four items), organization (three items), and Muhammadiyah goals (six items). The instrument fulfills the validity criteria since it has a loading factor between 0.3-0.85(>0.3) and CR 0.92 (>0.7). The instrument is reliable since Cronbach's Alpha is 0.869>0.7. Since it is valid and reliable, then it is suitable to be used to measure the views on Muhammadiyah ideology in Indonesia.